Social assistance programmes in South Asia: An analysis of socio-economic impacts - Yannick Markhof; Isabela Franciscon; Nicolò Bird; Pedro Arruda (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
Over the last two decades, the number of social assistance programmes has increased across South Asia, as changes in government policies and unprecedented economic growth have led to greater domestic attention to poverty alleviation and social exclusion. This report provides a critical review of the literature to summarise the impacts of different types of social assistance on socio-economic outcomes across South Asian countries
Keywords: 330; social protection; social assistance; South Asia